Bibliometric Analysis of Magnetite Nanoparticle Production Research During 2017-2021 Using Vosviewer - Agung Slamet Nugraha (Indonesian Journal of Multidiciplinary Research, 2022)
Fe3O4 nanoparticles are magnetic materials that can use in various fields. Fe3O4 particles have several properties such as being super magnetic, having a high saturation field, being chemically stable, biocompatibility, and low production costs. The purpose of this study was to conduct a bibliometric analysis of the research on the production of Fe3O4 nanoparticles by using mapping analysis with VOSviewer software. The data used in the study were obtained and collected using the Publish or Perish software. The data obtained were obtained based on the keywords "magnetite, nanomaterial, Fe3O4 nanoparticle, production". Based on the analysis conducted, it was found that 994 articles relevant to the keywords used were obtained in the 2017-2021 range. The results show that the production of Fe3O4 nanoparticles increased from 2017-2019 and decreased after that. This research is expected to help and become a reference for other researchers as consideration for determining the research theme to be taken.